A new species of planthopper in the genus Tico (Hemiptera: Auchenorrhyncha: Derbidae) on palms in Costa Rica - Echavarria, Marco A. Zumbado; Barrantes Barrantes, Edwin A.; Helmick, Ericka E.; Bartlett, Charles R.; Bahder, Brian W. (Zootaxa, 2022)
Tico is a small genus of planthopper comprised of four species primarily known from Costa Rica, with one species known from Trinidad and Venezuela. Recent survey work has documented multiple new species from palms and other broadleaf monocots in Costa Rica. Herein, a new species, Tico villablanca sp. n., is described from palms in the Los Angeles cloud forest, Costa Rica. Novel molecular data for the 18S rRNA gene and cytochrome c oxidase subunit I (COI) gene is provided for the new species and supplements morphological support for placement in the genus Tico. An updated key is provided for the species of Tico.